A comparative political economy of regional migration and labour mobility in West and Southern Africa. Issue 153 (3rd July 2017) - Cross, Hannah; Cliffe, Lionel
ABSTRACT: Based on a collaboration with the late Lionel Cliffe, this article suggests agendas and methods for analysing regional patterns of migration and labour mobility in Southern and West Africa. It locates local communities in regional patterns and global processes using two key organising concepts: first, the regionalisation of Africa, as outlined in Samir Amin's work. The authors consider continuities and discontinuities with the paradigms of 'Africa of the labour reserves' and 'Africa of the colonial trade economy' to understand contemporary realities. Second, this article explores the mechanisms and characteristics of cheap labour on different scales of analysis. This includes a discussion of the theories that explored the relations of reproduction of labour, and the reproduction of the labour system as a whole. In doing so, it rethinks the modes of production discourse to highlight the continuing importance of situations where capitalism exists alongside non-capitalist relations of production and reproduction.